2020
DOI: 10.2174/1381612826666200403120448
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Eugenol Derivatives and Evaluation of their Antifungal Activity Against Fusarium solani f. sp. piperis

Abstract: Background: Fusarium solani f. sp. piperis is a phytopathogen that causes one of the most destructive diseases in black pepper crops, resulting in significant economic and crop production losses. Consequently, the control of this fungal disease is a matter of current and relevant interest in agriculture. Objective: The objective was to synthesize eugenol derivatives with antifungal activity. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…We used the eugenol phenol group for structural modifications by bimolecular nucleophilic substitution approaches and copper(I)‐catalyzed azide‐alkyne cycloaddition (CuAAC) reaction. The synthesis and spectroscopic characterization of compound 1a‐d were recently reported (Maximino et al, 2020). We used spectrometric and spectroscopic methods such as uni‐ and bidimensional NMR and FT‐IR to characterize the chemical structures of new compounds ( 2f‐m ) (Data shown in Supplementary material; Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the eugenol phenol group for structural modifications by bimolecular nucleophilic substitution approaches and copper(I)‐catalyzed azide‐alkyne cycloaddition (CuAAC) reaction. The synthesis and spectroscopic characterization of compound 1a‐d were recently reported (Maximino et al, 2020). We used spectrometric and spectroscopic methods such as uni‐ and bidimensional NMR and FT‐IR to characterize the chemical structures of new compounds ( 2f‐m ) (Data shown in Supplementary material; Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The system remained for 30 min in this condition. Commercial halides (1.5 equivalent) ( a – c, e are bromides and d is chloride) were then added, and the system was kept at room temperature under stirring for 12 h. The reactions solutions were concentrated under reduced pressure and the final products purified by column chromatography using silica gel as the stationary phase and hexane: acetate (7:3, v/v) as mobile phase to obtain compounds 1a–e (Maximino et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also displays low chemical stability and is sensitive to oxidation and various chemical interactions [ 13 ]. To mitigate these side effects and to improve the biological profile of this molecules, various modifications of the structure of this molecule have been carried out [ 13 , 23 ]. In a previous study, it was reported that eugenol tosylate and its congeners, prepared by the functionalization of the hydroxyl group of eugenol with different sulfonyl chlorides under basic conditions, showed promising antifungal activities compared to eugenol.…”
Section: Resultsmentioning
confidence: 99%
“…Its derivatives exhibit leishmanicidal, insecticidal, anti-inflammatory, antibacterial, antioxidant properties. Notably, extensive chemical modification of eugenol has resulted in substances with antifungal activity. …”
Section: Introductionmentioning
confidence: 99%